KEEFEKTIFAN METODE KALIMAT KONTEKSTUAL DAN FUNGSIONAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK DOWN SYNDROME - Yury Ulandary, - (2021)
Early reading is a fundamental reading ability that indicates that the child can understand letters, syllables, words, and sentences in written into spoken form. Limitations in intellectual make children with Down Syndrome have difficulty in the early reading stage, because the methods are used today are not based on the learning principles of children with Down Syndrome. So, we need a method that is expected to allow children to understand writings that can provide useful information in their environment. Based on the research problems, the purpose of this study was to determine 1) The objective condition of the reading ability of Children with Down Syndrome before being given treatment; 2) Formulate the contextual and functional sentence method draft to improve the early reading ability of Children with Down Syndrome; 3) recognize the effectiveness of the contextual and functional sentence method to improve the early reading ability of children with Down Syndrome. This study uses a quantitative approach with an experimental Single Subject Research (SSR) design method. The subjects in this study are two children with Down Syndrome on grade fifth at SLBN A Citeureup. The obtained data are the result from the test using descriptive percentage analysis. The results showed that the application of contextual and functional sentence methods effectively improved the early reading ability of children with Down Syndrome. So, it is recommended to teachers as an alternative for early reading learning of children with Down Syndrome.